2008
DOI: 10.1056/nejmoa071804
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stents vs. Coronary-Artery Bypass Grafting in Multivessel Coronary Disease

Abstract: For patients with multivessel disease, CABG continues to be associated with lower mortality rates than does treatment with drug-eluting stents and is also associated with lower rates of death or myocardial infarction and repeat revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
146
1
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(168 citation statements)
references
References 27 publications
9
146
1
12
Order By: Relevance
“…The findings of these studies are consistent with ours because the relative outcomes associated with the two procedures were similar across quartiles [1] or quintiles [17] of PS or terciles of EuroSCORE and SYNTAX Score [4] . The categorization adopted in these studies may, however, have been too broad to unveil the heterogeneity of treatment-effect estimates [18,19] , while the one adopted here should yield stronger evidence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of these studies are consistent with ours because the relative outcomes associated with the two procedures were similar across quartiles [1] or quintiles [17] of PS or terciles of EuroSCORE and SYNTAX Score [4] . The categorization adopted in these studies may, however, have been too broad to unveil the heterogeneity of treatment-effect estimates [18,19] , while the one adopted here should yield stronger evidence.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of severe Coronary Artery Disease (CAD) (left main or multivessel involvement) -the scientific evidence [1][2][3][4][5][6][7][8][9] supporting the interventional choice between Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Graft (CABG) is inconclusive. Uncertainty surrounds not only the 'best' technique in absolute terms (i.e.…”
mentioning
confidence: 99%
“…CABG might be more beneficial than PCI in octogenarians regardless of sex. 24,25 Third, because more patients underwent PCI in the later cohort, the followup duration was longer in the CABG group than in the PCI group. The risk of PCI relative to CABG might be different according to the follow-up duration after the index procedure.…”
mentioning
confidence: 99%
“…In most clinical trials comparing PCI and CABG for the treatment of ULMCA disease, patients with severe left ventricular dysfunction were excluded, 11,12 and several registry studies and randomized trials showed conflicting clinical outcomes of PCI, CABG, or medication for patients with decreased systolic function. [27][28][29] Subsequent randomized trials will be critically important for the development of optimal treatment strategies for patients with CAD, heart failure, and severe left ventricular systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%